Embeddedness of enterprises prior to and during early internationalization : multiple case study of Finnish life-science companies - Vuorinen, Petra (2018)
The aim of this master’s thesis was to understand the meaning of network structures and embeddedness of the Finnish SMEs when they begin the process of internationalization. All firms form network ties, but the depth and strength of the ties seem to vary significantly between companies. The theoretical understanding of embeddedness has remained rather incomplete and it seems that the research domain would benefit of a stronger emphasis on the first steps of the internationalization, the time frame of highest uncertainty. Additionally, more profound understanding of the strategies that Finnish SMEs follow during the early internationalization is needed. The study was carried out as a case-based research, and the empirical data was collected through narrative, non-directive interviews of six Finnish life-science SMEs. Interview data was analyzed by qualitative method, and timelines of each company were drawn in order to evaluate both international orientation of the case companies, and embeddedness of their networks. The findings suggest that Finnish life-science SMEs tend to start internationalizing with niche products, which do not possess big sales volumes in one country, and therefore they very soon need to find several export markets and several partners. The narratives reflected both proactive and reactive behavior in the process of internationalization, and even thought the case companies were chosen from the same industry, the internationalization stories varied considerably. The timelines of the companies confirmed that often the decisions and operations of the firms reflect the company strategy as such. All of the case entrepreneurs were well aware about the importance of networks and embeddedness. Strong ties were seen essential, especially when aiming for long-term customer relationships, but they could also easily create undesired dependence between the partners. Most of the case companies had formed clear internationalization plans and strategic goals, but still they had been surprised by the significant role of socializing, dining and trust-building when creating their first international business relationships.